Trimester effects of source-specific PM10 on birth weight outcomes in the Avon Longitudinal Study of Parents and Children (ALSPAC) - Chen, Y; Hodgson, S; Gulliver, J; Granell, R; Henderson, AJ; Cai, Y; Hansell, AJ (BioMed Central, 2021)
Background Evidence suggests that exposure to particulate matter with aerodynamic diameter less than 10 μm (PM10) is associated with reduced birth weight, but information is limited on the sources of PM10 and exposure misclassification from assigning exposures to place of residence at birth.